Análisis de prácticas sustentables en empresas de La Plata, provincia de Buenos Aires - Solari, Estefanía (2023)
Given the need for governments in the region to promote policies that encourage the adoption of sustainable practices by the private sector. Some of the basic works of the present have been Alizadeh, (2022), Bux et al. (2020), Costache et al. (2021) and Zou et al. (2021). The objectives were: to evaluate the sustainable practices implemented by the companies and investigate the relationship with the university educational level of the person responsible for the company, the longevity of the company, the percentage of women employees, the lack of knowledge and the lack of financial resources. To comply with these, a survey of companies in the La Plata region was carried out in November 2022, using a quantitative research approach and a binary logit model. Results highlighted increased implementation of sustainable practices in areas such as customer engagement, regulatory compliance and labor practices. Among the variables studied, only the age of the company and the lack of knowledge proved to be statistically significant in explaining the level of implementation of sustainable practices, corroborating previous research (Alizadeh, 2022; Costache et al., 2021; Mahmood et al., 2021; Peter, 2017; Yeh et al., 2014).